Empowering future pharmacists: CEO insights / Nurul Ain Najwa Mohd Azmin and Aida Azlina Ali - Mohd Azmin, Nurul Ain Najwa; Ali, Aida Azlina (Faculty of Pharmacy, 2024)
On June 19, 2024, the Faculty of Pharmacy at UiTM Puncak Alam was abuzz with excitement as it hosted the much-anticipated "CEO Insights" programme in collaboration with Pfizer Malaysia Sdn. Bhd. The event, held at DK500, aimed to provide undergraduate pharmacy students with a unique opportunity to engage with leaders in the pharmaceutical industry.